2006
DOI: 10.1111/j.1574-6941.2006.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Litter-forager termite mounds enhance the ectomycorrhizal symbiosis between Acacia holosericea A. Cunn. Ex G. Don and Scleroderma dictyosporum isolates

Abstract: The hypothesis of the present study was that the termite mounds of Macrotermes subhyalinus (MS) (a litter-forager termite) were inhabited by a specific microflora that could enhance with the ectomycorrhizal fungal development. We tested the effect of this feeding group mound material on (i) the ectomycorrhization symbiosis between Acacia holosericea (an Australian Acacia introduced in the sahelian areas) and two ectomycorrhizal fungal isolates of Scleroderma dictyosporum (IR408 and IR412) in greenhouse conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Soil foraging termite mounds like those of Macrotermes falciger play an important part in ecosystem functioning, even in their whole landscape structuring : they influence community-wide interactions via changes in the abiotic landscape and induce biological diversity as well as landscape heterogeneity [7, 10, 29, 30]. Their action in the soil, as presented in the discussion, influences resources distribution, which favours the development of microbial activity as well as symbiotic ectomycorhizes on plants growing on the mounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil foraging termite mounds like those of Macrotermes falciger play an important part in ecosystem functioning, even in their whole landscape structuring : they influence community-wide interactions via changes in the abiotic landscape and induce biological diversity as well as landscape heterogeneity [7, 10, 29, 30]. Their action in the soil, as presented in the discussion, influences resources distribution, which favours the development of microbial activity as well as symbiotic ectomycorhizes on plants growing on the mounds.…”
Section: Discussionmentioning
confidence: 99%
“…Their action in the soil, as presented in the discussion, influences resources distribution, which favours the development of microbial activity as well as symbiotic ectomycorhizes on plants growing on the mounds. This favours their development and increases nitrogen content in the soil through atmospheric nitrogen fixation by the mycorhizes [29, 30]. Due to this richer soil composition on termite mounds, specific vegetation develops, inducing new ecosystems locally and heterogeneous patterns in the landscape [10, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Bama and Ravindran (2018) concluded that combined use of termite mound materials and inorganic fertilization significantly increase the Zea mays growth and yield. Kisa et al (2006) showed that termite mound materials consisting of Pseudomonas monteilii species enhanced the ectomycorrhizal development between Acacia holosericea and Scleroderma dictyosporum. Suzuku et al (2007) observed that combining sandy soil with termite mound materials at a proportion of 120 Mg/ha improved porosity and transformed the pore size distribution, thus causing a stepping up in the obtainable water content for the crop growth.…”
Section: Termitesmentioning
confidence: 99%